Accounting for the effect of particle density and size on stratification in mineral jigs: A preliminary model based on particle settling rates. (15th March 2022) - Woollacott, L.C.
Highlights: Arbitrary assumptions are made to King's stratification model to account for particle size. The driving force for stratification is assumed to be the difference between particle settling rates. A simple model for particle settling rates in a jigging environment is developed. The expanded stratification model fits experimental data for three stratification contexts very well. Abstract: A model is developed that accounts for the effect of particle density and size on stratification in mineral processing contexts. It is based on the premise that stratification is driven by differences in the settling rates of particles in a stratifying particle bed. A number of arbitrary assumptions are made to avoid the complications associated with modelling settling rates in that environment. Despite the arbitrariness and simplicity of the assumptions made, the model fits stratification data remarkably well. It reduces to the well-validated King model in the context of density stratification, and also fits size stratification data very well. In more general contexts where both particle density and size vary, the fits to experimental data are also good although some anomalies occur. Better fits are anticipated from a more rigorously derived version of the model that is presented in a follow up paper.